Relationship between auditor integrity and organizational commitment to fraud prevention - Mohammad Husen Rifai; Agus Widodo Mardijuwono (Asian Journal of Accounting Research, 2020)
The purpose of this research is to obtain empirical evidence about the impact of auditor’s integrity and organizational commitment to the prevention of fraud.This research was conducted using questionnaires distributed to all internal auditors who worked at East Java Representatives Office of Indonesia’s National Government Internal Auditor. One hundred and thirteen questionnaires were distributed, and fifty-seven questionnaires were received, and all have validity eligible to use in this research. The hypothesis of this research was tested using the partial least square analysis with WarpPLS version 6.0 software.The result of this research found that auditor’s integrity and organizational commitment affect positively to fraud prevention.Using government internal auditors, this study believed, brings a new insight into government internal auditor behavior.